Research of fitobioti (ІІ th opened convention of fitobiologiv Kherson, Kherson, on May, 15 2008) (CHORNOMORSKI BOTANICAL JOURNAL, 2007)
Research of fitobioti (ІІ th opened convention of fitobiologiv Kherson, Kherson, on May, 15 2008)